2023
DOI: 10.3390/ijerph20043319
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and Depression Levels and Coping Strategies among Polish Healthcare Workers during the COVID-19 Pandemic

Abstract: During the COVID-19 pandemic, medical staff were commonly exposed to stress, work under pressure, and long shifts, and may have experienced a fear of infecting loved ones or a fear for their own health. All of these factors may have increased the likelihood that healthcare workers will experience the symptoms of depression, anxiety, or other mental health disorders. In this cross-sectional study, a group of respondents was gathered from the employees of 78 hospitals in Poland. A questionnaire was completed ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Long COVID has long-term heterogeneity and complex symptoms [66]. The most common symptoms include chronic fatigue [67]; respiratory manifestations (e.g., cough and shortness of breath) [67]; arrhythmias, palpitations, hypotension, increased heart rate, venous thromboembolic disease, myocarditis, and acute heart failure [68]; and symptoms of neurological and psychiatric related disorders (e.g., peripheral neuropathy, brain fog, anxiety, and depression) [67,69,70]. Diagnostic clusters have shown that long COVID does not have a single phenotype but, instead, a collection of sub-phenotypes subject to different diagnoses and treatments [71].…”
Section: Long Covidmentioning
confidence: 99%
“…Long COVID has long-term heterogeneity and complex symptoms [66]. The most common symptoms include chronic fatigue [67]; respiratory manifestations (e.g., cough and shortness of breath) [67]; arrhythmias, palpitations, hypotension, increased heart rate, venous thromboembolic disease, myocarditis, and acute heart failure [68]; and symptoms of neurological and psychiatric related disorders (e.g., peripheral neuropathy, brain fog, anxiety, and depression) [67,69,70]. Diagnostic clusters have shown that long COVID does not have a single phenotype but, instead, a collection of sub-phenotypes subject to different diagnoses and treatments [71].…”
Section: Long Covidmentioning
confidence: 99%
“…Throughout the COVID-19 pandemic, HCPs reported turning to friends and family for support, exercising, substance use, spiritual/religious practice, meditation and psychological well-being apps to manage the stresses associated with their occupational roles [17][18][19][20]. For example, among HCPs in Poland during the COVID-19 pandemic, Budzy ńka and Moryś [21] reported that HCPs most commonly engaged in denial, substance use and the cessation of usual activities in relation to the demands of their workplace between August 2021 and March 2022. Notably, these behaviors may in turn be associated with long-term mental health deterioration [21].…”
Section: Introductionmentioning
confidence: 99%
“…For example, among HCPs in Poland during the COVID-19 pandemic, Budzy ńka and Moryś [21] reported that HCPs most commonly engaged in denial, substance use and the cessation of usual activities in relation to the demands of their workplace between August 2021 and March 2022. Notably, these behaviors may in turn be associated with long-term mental health deterioration [21]. Alternatively, Haor et al [22] reported that Polish nurses primarily engaged in problem-focused coping (i.e., planning, counselling, seeking support) in response to pandemic stressors between November and December 2021, which may be associated with a reduction in burnout.…”
Section: Introductionmentioning
confidence: 99%